Pendampingan keuangan dan pemasaran lele asap hasil budidaya bioflok di Gampong Buket Kabupaten Aceh Utara (Financial assistance and marketing of smoked catfish from biofloc cultivation in Bukit Village, North Aceh District) - Asbar, Yuli; Iswadi, I; Muliani, M; Erlangga, E; Biby, Sapna (Buletin Pengabdian, 2023)
Fish farmers in Buket village already have basic catfish farming skills using soil ponds and biofloc. Obstacles occur when harvesting catfish simultaneously causes oversupply so that catfish prices fall and if they are not harvested immediately, farmers will experience losses due to feed needs that continue to increase along with the growth of catfish. Therefore, the purpose of this service activity is to manage financial management and help market the results of catfish rearing with biofloc technology that is converted into smoked catfish, and increase the value of the results of processing smoked catfish products. This service activity uses educational, participatory, survey, and persuasive methods. This community service activity consists of several stages, namely: (1) Socialization and coordination of activities (2) catfish smoking techniques (3) smoked catfish marketing techniques. Evaluation of service participants' success and satisfaction rate was carried out using a questionnaire. Based on the analysis of the level of satisfaction and success 80-90% of partners are satisfied with this service activity. This service activity provides positive knowledge and motivation to partners.